2015
DOI: 10.1007/s10955-014-1173-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Random Dispersion Help Survival?

Abstract: Many species live in colonies that prosper for a while and then collapse. After the collapse the colony survivors disperse randomly and found new colonies that may or may not make it depending on the new environment they find. We use birth and death chains in random environments to model such a population and to argue that random dispersion is a superior strategy for survival.Keywords Stochastic model · Random environment · Survival strategy The ModelMany species (such as ants or early humans) survive accordin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
0
7
0
8
Order By: Relevance
“…Colonies collapse independently of each other at rate a > 0. The proof in Schinazi (2015) may be adapted to show that survival has positive probability if and only if…”
Section: Non Spatial Modelsmentioning
confidence: 99%
“…Colonies collapse independently of each other at rate a > 0. The proof in Schinazi (2015) may be adapted to show that survival has positive probability if and only if…”
Section: Non Spatial Modelsmentioning
confidence: 99%
“…Individuals of these populations disperse, trying to make new colonies that may succeed settling down depending on the new environment they encounter. Recently, Schinazi [9] and Machado et al [7] proposed stochastic models for this kind of population dynamics. For these models they concluded that dispersion is a good survival strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the model proposed by Artalejo et al [1], and adapting some ideas from Schinazi [9] and Machado et al [7], we analyze growth models of populations subject to disasters, where after the collapse species adopt dispersion as a survival strategy. We show that dispersion is not always a good strategy to avoid the population extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Esses indivíduos se dispersam tentando fazer novas colônias que podem ou não se estabelecer dependendo do ambiente que encontram. Recentemente, Schinazi [20] propôs um modelo estocástico não espacial para modelar tal tipo de dinâmica populacional e mostrou que a dispersão aleatóriaé uma boa estratégia para a sobrevivência da população. O modelo e os principais resultados em Schinazi [20] estabelecem o seguinte.…”
Section: Estratégias De Sobrevivênciaunclassified
“…Recentemente, Schinazi [20] propôs um modelo estocástico não espacial para modelar tal tipo de dinâmica populacional e mostrou que a dispersão aleatóriaé uma boa estratégia para a sobrevivência da população. O modelo e os principais resultados em Schinazi [20] estabelecem o seguinte. Teorema 1.2.1 (Teorema 1 em [20]).…”
Section: Estratégias De Sobrevivênciaunclassified